Hajj and Social Mobility of Bugis Women - Muhammadiyah, Hilmi (Mimbar Agama Budaya, 2022)
The lifestyle of the Bugis people has shifted since the presence of Islam. The Bugis people no longer refer to local traditions and customs but are starting to pay attention to Islamic values. So that the movement of the Bugis community cannot be separated from Bugis traditions or customs and Islamic teachings. The well-known Bugis culture is Panngaderreng, the five values of life resulting from joint deliberations on trades and Islamic studies. The panngaderreng formulation requires that Islam be placed as a teaching that must be side by side with the customs and culture of the Bugis community in any sector. It is different from the pilgrimage ritual. In the Bugis tribe, women get a more significant opportunities than men. This is based on the level of interest of Bugis women in the pilgrimage ritual. They place Hajj as a religious status that has a delay because Islamic teachings have only been echoed in this new era compared to their traditions or customs. The method used in this paper is to use a qualitative approach with a literature review (literature review). A literature study was conducted through written data using content analysis. This technique helps obtain a theoretical basis by reviewing and studying books, documents, and research results related to the social mobility of Bugis women.